Regulation of Brassinosteroid Homeostasis in Higher Plants - Wei, Zhuoyun; Li, Jia (Frontiers in Plant Science, 2020)
Brassinosteroids (BRs) are known as the sixth class of phytohormones essential for various processes during normal plant growth, development and adaptations to biotic and abiotic stresses. Significant progress has been achieved on revealing mechanisms regulating BR biosynthesis, catabolism and signaling in many crops as well as in model plant Arabidopsis. It is known that BRs control plant growth and development in a dosage-dependent manner. Maintenance of BR homeostasis is therefore critical for optimal functions of BRs. In this review, updated discoveries on mechanisms controlling BR homeostasis in higher plants in response to internal and external cues are discussed.